Ecological strategies and impact of wild boar in phytogeographic provinces of Argentina with emphasis on Aridlands - Cuevas, Maria Fernanda (2016)
Wild boar is an invasive species introduced to Argentina for sport hunting purposes. Here, this species is present in at least 8 phytogeographic provinces but we only have information in four of them (Pampean grassland, Espinal, Subantarctic and Monte Desert). We review the ecological strategies and impact of wild boar on ecosystem processes in these different phytogeographic provinces and identify knowledge gaps and research priorities for a better understanding of this invasive species in Argentina. We observe that foraging strategies ofwild boar consist in consuming mainly plant species rich in energy, especially those with bulbs and fuits having high concentrations of carbohydrates and lipids, and the use of habitat is closely associated with food resource availability. Wild boar generate a broad variety of impacts reflected in plant species composition, structure and biomass, and changes in soil properties such as increased soil degradation in the Monte Desert. We conclude that the impacts of wild boar in Argentina are mostly negative, demanding more interaction among relevant players (scientists, government officials, managers of protected areas, and landowners) to plan the population control strategies needed to mitigate damage to native ecosystems and agricultural production in the country.